Effect of dietary supplementation of plantain herb, lemongrass and their combination on milk yield, immunity, liver enzymes, serum, and milk mineral status in dairy cows - Rahman, Md Aliar; Redoy, Md Rahat Ahmad; Chowdhury, Rakhi; Al Mamun, Mohammad (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This research aimed to assess the effects of dried plantain herb, lemongrass, and their combination on milk yield, immunological, liver enzymatic, serum, and milk mineral status in dairy cows. Materials and Methods: Twenty cows were arbitrarily assigned to 4 diets. Cows were given a basal ration considered as control diet (CL-D) having 14.93% crude protein (CP)and 10.96 MJ ME per kg dry matter (DM). Each cow was given 100 gm plantain, 100 gm lemongrass, and 50 gm plantain + 50 gm lemongrass with CL-D and taken as plantain diet (PT-D), lemongrass diet (LG-D), and plantain-lemongrass diet (PL-D), daily for 63 days, respectively. Blood and milk samples were taken four times at an interval of 14 days. Data were analyzed using a two-way repeated measures analysis of covariance. Results: Better DM consumption and milk yield were observed in the PT-D and LG-D compared to the CL-D (p ≤ 0.05). LG-D improved the milk’s total solids, protein, and fat compared to CL-D (p < 0.05). Substantially, herbal groups improved serum albumin and reduced globulin concentrations compared to CL-D. LG-D had the highest serum immunoglobulin G, while herbal groups effectively reduced the liver enzymes compared to CL-D. Herbal groups did not affect serum and milk’s calcium and phosphorus concentrations, while LG-D and PL-D substantially improved serum and milk zinc concentrations. Conclusions: Both plantain and lemongrass improved dairy cows’ DM consumption and milk yield. Plantain and/or lemongrass enhanced the immune system and liver health, but not serum and milk calcium and phosphorus level. Lemongrass and a combination of plantain and lemongrass increased the serum and milk zinc concentrations. Adv. Vet. Anim. Res., 11(1): 185-193, March 2024 http://doi.org/10.5455/javar.2024.k764